2018
DOI: 10.1007/jhep02(2018)092
|View full text |Cite
|
Sign up to set email alerts
|

Loopholes in Z′ searches at the LHC: exploring supersymmetric and leptophobic scenarios

Abstract: Searching for heavy vector bosons Z , predicted in models inspired by Grand Unification Theories, is among the challenging objectives of the LHC. The ATLAS and CMS collaborations have looked for Z bosons assuming that they can decay only into Standard Model channels, and have set exclusion limits by investigating dilepton, dijet and, to a smaller extent, top-antitop final states. In this work we explore possible loopholes in these Z searches, by studying supersymmetric as well as leptophobic scenarios. We demo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 69 publications
1
31
0
Order By: Relevance
“…The severest bound on M Z comes from negative results from the LEP data as M Z /g B−L ≥ 6 TeV [65]. Even though considering its decay modes can lower the mass bound on Z [14][15][16][17], setting M Z ≥ 4 TeV [18] guarantees avoiding possible exclusions on our solutions due to the light Z mass. Thus we restrict its range in our scan as…”
Section: Jhep01(2021)161mentioning
confidence: 99%
See 1 more Smart Citation
“…The severest bound on M Z comes from negative results from the LEP data as M Z /g B−L ≥ 6 TeV [65]. Even though considering its decay modes can lower the mass bound on Z [14][15][16][17], setting M Z ≥ 4 TeV [18] guarantees avoiding possible exclusions on our solutions due to the light Z mass. Thus we restrict its range in our scan as…”
Section: Jhep01(2021)161mentioning
confidence: 99%
“…There appears a Z gauge boson together with its SUSY fermion partnerB . The search for Z such as this is a major focus of the recent and planned experiments [14][15][16][17][18]. Our investigation is based on the model proposed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the current mass bounds on Z 0 are established as M Z 0 ≳ 4.1 TeV [18]. On the other hand, this bound can vary model dependently, and a most recent study [47] has shown that M Z 0 ≳ 2.5 TeV can survive, if Z 0 is leptophobic. Based on our previous study [19], which was conducted in the similar parameter space, the leptonic decay processes of Z 0 are found as BRðZ 0 → llÞ ≲ 14%.…”
Section: Scanning Procedures and Experimental Constraintsmentioning
confidence: 99%
“…These models can be rendered leptophobic by using kinetic mixing between the two U (1) gauge groups, as in e.g. [37].…”
Section: Introductionmentioning
confidence: 99%